Echocardiography in PICU: when the heart sees what is invisible to the eye - Fatma Rabah; Khalfan Al-Senaidi; Ismail Beshlawi; Alddai Alnair; Anas-Alwogud Ahmed Abdelmogheth (Elsevier, 2016)
ABSTRACT OBJECTIVE: Echocardiography has become an indispensable bedside diagnostic tool in the realm of pediatric intensive care units (PICU). It has proven to be an influential factor in the formula of clinical decision-making. This study aimed to delineate the impact of echocardiography on the management of critically ill pediatric patients in the PICU at Sultan Qaboos University Hospital, Oman. METHOD: This was a retrospective cohort study conducted in a five-bed PICU. Patients admitted to the PICU from January of 2011 to December of 2012 were reviewed. Those who have undergone bedside echocardiography during their ICU stay were recruited. Electronic patient record was used as data source. RESULTS: Over a-24-month period, 424 patients were admitted in this PICU. One hundred and one clinically indicated transthoracic echocardiograms were performed. 81.8% of these presented new findings (n = 82) that significantly impacted the clinical decision of patient management, namely, alteration in drug therapy and procedure, whereas no difference in the management was yielded in the remaining 17.8% of the studied cases. CONCLUSIONS: Echocardiography had a significant impact on the management of PICU patients. Such salutary effect was consequently reflected on the outcome. Pediatric intensivists are encouraged to acquire such bedside skill.